O indianismo em Americanas (1875), de Machado de Assis (releitura da tradição romântica) - Grandolpho, Marina Venâncio (2014)
This dissertation will seek to understand the issues existing at the time of publication of the book Americanas (1875) written by Machado de Assis. For this, we will hold a course by the Brazilian Romanticism, considering one of its main elements: Indianism, and reading of Americanas in the prism of the american Indian-Romantic tradition. Through this course we aim to see how the reading of Americanas worked the Indianism in the book, discuss the theme distancing at the time of its publication as a rereading of this romantic tradition and elucidate the facts that lead to the writer's choice for this theme, dear to the romantic nationalist project, thus showing the possibility of a distinct nationalism embedded in this work.